2020
DOI: 10.1177/0267659120952982
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Xa versus time-guided anticoagulation strategies in extracorporeal membrane oxygenation: a systematic review and meta-analysis

Abstract: The purpose was to compare time-based vs anti-Xa-based anticoagulation strategies in patients on ECMO. We conducted a systematic review and meta-analysis using multiple electronic databases and included studies from inception to July 19, 2019. The proportion of bleeding, thrombosis, and mortality were evaluated. Twenty-six studies (2,086 patients) were included. Bleeding occurred in 34.2% (95%CI 25.1;43.9) of the patients with anti-Xa-based versus 41.6% (95%CI 24.9;59.4) of the patients with time-based antico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 57 publications
0
22
2
1
Order By: Relevance
“…In a systematic review, Willems et al ( 24) compared time-guided vs. anti-factor Xaguided anticoagulation strategies for UNFH titration in patients on ECMO. This meta-analysis showed that an anti-factor Xa-based anticoagulation strategy was associated with fewer hemorrhagic complications without an increase in thrombotic events, when compared to a time-based anticoagulation strategy (24). In contrast to these findings, we found no differences regarding anti-factor Xa values, when comparing the groups with and without bleeding events.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In a systematic review, Willems et al ( 24) compared time-guided vs. anti-factor Xaguided anticoagulation strategies for UNFH titration in patients on ECMO. This meta-analysis showed that an anti-factor Xa-based anticoagulation strategy was associated with fewer hemorrhagic complications without an increase in thrombotic events, when compared to a time-based anticoagulation strategy (24). In contrast to these findings, we found no differences regarding anti-factor Xa values, when comparing the groups with and without bleeding events.…”
Section: Discussioncontrasting
confidence: 90%
“…However, we did not compare two different anticoagulation strategies. Nevertheless, the results shown in the study by Willems et al (24) could suggest that an anti-factor Xa-based UNFH titration strategy could also reduce bleeding complications in neonatal patients on ECMO.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, close monitoring of all hematologic parameters, including VET and personalized antithrombotic therapy, is recommended in patients with severe COVID-19, particularly during ECMO support [29]. The degree of anticoagulation can be assessed based on the anti-Xa activity or INTEM/HEPTEM CT-ratio for UFH, anti-Xa activity or NATEM/NAHEPTEM CT-ratio for LMWH, and anti-IIa activity, EXTEM CT, or ECATEM/ECA-test CT for IV direct thrombin inhibitors such as argatroban and bivalirudin [65,73,74,[85][86][87][88][89][90].…”
Section: Bleeding In Patients With Covid-19mentioning
confidence: 99%
“…1A,B). Considering the limitation of APTT in monitoring UFH [33], and the recommendation of anti‐FXa assays in the application of UFH determination [34,35], the anti‐FXa assays and turbidity assays were chosen to determine the potency of PS and R15, followed by verification in rats in vivo .…”
Section: Discussionmentioning
confidence: 99%